Analysis of subthreshold swing in junctionless double gate MOSFET using stacked high-k gate oxide - Jung, Hakkee (Institute of Advanced Engineering and Science, 2021)
In this paper, the subthreshold swing was observed when the stacked high-k gate oxide was used for a junctionless double gate (JLDG) MOSFET. For this purpose, a subthreshold swing model was presented using the series-type potential model derived from the Poisson equation. The results of the model presented in this paper were in good agreement with the two-dimensional numerical values and those from other papers. Using this model, the variation of the subthreshold swing for the channel length, silicon thickness, gate oxide thickness, and dielectric constant of the stacked high-k material was observed using the dielectric constant as a parameter. As a result, the subthreshold swing was reduced when the high-k materials were used as the stacked gate oxide film. In the case of the asymmetric structure, the subthreshold swing can be reduced than that of the symmetric JLDG MOSFET when the dielectric constant of the bottom stacked oxide film was greater than that of the top stacked oxide film. In the case of the asymmetric structure, the subthreshold swing could be also reduced by applying the bottom gate voltage lower than the top gate voltage.